Propuesta de un modelo de gestión administrativo para la unidad de medio ambiente del GAD cantón Jama - Andrade Reyes, Sergia Maribel (2014)
This research was conducted in the GAD of Jama cantón, in order to propose a management model to improve the service to the user and administrative activities of this department. Within this area are given services directed to the treatment of solid waste through recycling and landfill, but present shortcomings in the administrative field that is necessary to implement a management model. The objective of this research was a situational diagnosis of the unit of environment through a SWOT matrix, determine a methodological process to develop the management CAF model to evaluate the service provided by this office, search for information by different authors served as the basis for this research, an interview with the head of the department applying an assessment based under the criteria of the model, then the measurement of satisfaction of the user by means of a survey, also a Deming matrix was developed to organize the process for a continuous improvement to develop an environment of the canton in Jama, a plan of action for improvement that contributes to the administration of this department are socialized with the authorities of the canton.